SOSIALISASI PENTINGNYA ETIKA PROFESI UNTUK MEMBENTUK KARAKTER - Purba, Hasian; Yudha, Fairas Panca (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2024)
BHS must prioritize assistance to groups, not individuals. There should be more legal aid in rural areas on the outskirts, because the oppressed layers are actually more numerous on the outskirts. If this rural-oriented legal aid can be used, then the central position will be easier to shake. Based on the events that have been described, problems were found that caused a lack of legal understanding and legal knowledge in the community, especially regarding the provisions of the Advokad code of ethics. As well as the ineffectiveness of legal regulations in accommodating every need of the general public. Through analysis of this proposal, the author determined a solution which includes, Providing information and outreach regarding regulations to the public to increase public understanding and knowledge. The solution recommended by the author is, Providing information and outreach regarding statutory regulations to the public, and holding PARALEGAL training for the general public, as well as providing easy access to free legal aid services to the public, in resolving any legal problems currently being faced.